2022
DOI: 10.1155/2022/3307873
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of SETDB1 Predicts Poor Prognosis in Multiple Myeloma

Abstract: Several genes on chromosome 1q21 region predict a high risk of multiple myeloma (MM); however, the underlying molecular pathology remains elusive. Overexpression, amplification, or activation of SET Domain Bifurcated 1 (SETDB1), which is located on 1q21, is closely associated with poor prognosis of many human solid malignancies. In our study, upregulation of SETDB1 might indicate an unfavorable prognosis of MM using bioinformatics analysis from GEO databases and MMRF-CoMMpass. Here, increased SETDB1 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In addition, the highest mCA cell fraction was observed in a man who was diagnosed with BL within days of baseline. His mCAs encompassed SETDB1 and SRSF2, both of which are mutated in other hematologic malignancies [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the highest mCA cell fraction was observed in a man who was diagnosed with BL within days of baseline. His mCAs encompassed SETDB1 and SRSF2, both of which are mutated in other hematologic malignancies [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…This KMT is a potential target in multiple signaling pathways of carcinogenesis. 31,32,34,78,79 Several studies have reported that the overexpression of SETDB1 and its activity are related to aggressive tumor phenotypes, 80 such as in breast, 35,81,82 colon, 83,84 liver 32,33,85 and lung cancers, 78,[86][87][88][89] as well as in myeloid leukemia. 90,91 Furthermore, lung cancer studies have shown that the upregulation of the protein was vital for its rapid growth and proliferation.…”
Section: Setdb1: Function In Cancer Contextmentioning
confidence: 99%
“…[128][129][130][131] Given the intricacy and significance of the immune response in cancer survival, some research has looked at the influence and function of SETDB1 in this scenario. 80,95,[132][133][134] For example, Griffin et al demonstrates SETDB1 as an immune escaping mediator and immune sensitivity modulator of cancer cells. More notably, the study demonstrated that, in patients with advanced renal cell carcinoma, SETDB1 amplification or overexpression also predicted poor prognosis in response to programmed death 1 (PD1) blockage but not mTOR inhibition.…”
Section: Setdb1 and Immunotherapymentioning
confidence: 99%
“…1. SETDB1 suppresses Th17 transcription and upregulates production of CD56dim natural killer cells [23]. SETDB1 suppresses IL‐6 production [13].…”
Section: Setdb1 Interferes With the Immune System Within Cancermentioning
confidence: 99%
“…As we previously mentioned, Hachiya and colleagues suggested that IL-6 expression in macrophages is mediated by TLR4 and induced by SETDB1 depletion [13]; confirmation of direct SETDB1-mediated expression still needs to be confirmed in future studies. Xiang and colleagues characterized the mechanism associating SETDB1 overexpression with poor prognosis of multiple myeloma [23]. Higher levels of SETDB1 correlates with higher levels of beta-2 microglobulin, lactate dehydrogenase (LDH), bone marrow biopsy plasma cells, and lower haemoglobin levels.…”
Section: Setdb1 Interferes With the Immune System Within Cancer Setdb...mentioning
confidence: 99%